The Principle IndecomposableProjective Characters of The Symmetric Groups S_22Modulo p=19 - Resen, Jenan AbdAlreda; Abbas, Shereen Jamel; Sadiqc, Haneen J. (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2020)
In this paper we invention all the principle indecomposablespin(projective) characters of the symmetric group when and the characteristic of the field is 19. The principle indecomposable spincharacters of the symmetric group ,also can get it by determine all irreducible spin characters for , and all irreducible modular spin characters for , the sum of multiplication of these characters it represents the principle indecomposable spin(projective) characters of the symmetric group .For their more can get on the irreducible spin characters for by fixing all bar partitions for , also we can get on all the irreducible modular spin characters for by -inducing method, finally induce the principal indecomposable characters(P.i.s)from (see creek*) give usprincipal indecomposable characters (P.i.s) or principal characters (P.s) of .